MOTIVASI INDONESIA MENERAPKAN KEBIJAKAN ANTI DUMPING TERHADAP IMPOR BAJA COLD ROLLED COIL (CRC) JEPANG TAHUN 2013 - Diah Dini Wati; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The focus of this research is to analyze the motivation of Indonesia to imposition of antidumping duty (BMAD) towards Japan’s cold rolled coil/CRC products in 2013. In investigation of The Indonesian Antidumping Committee (KADI) finds dumping in Cold Rolled Coil/CRC import from Japan and there was injury to the domestic industry.This research use a descriptive of qualitative method, Nation state analysis, protectionism theory in mercantilism perspective. To analyze this case, the writer collects data from books, journal, websites, dictionary, and final report of the Indonesian Anti Dumping Committee (final determination) on Antidumping investigation againts imports of cold rolled coil/CRC products from Japan, Korea, China, Taiwan, and Vietnam.The result of this research shows that Indonesia to imposition of Antidumping import duties on products import of Cold Rolled Coil/CRC to protect the Indonesia domestic industry from injury. In 19 march 2013 Indonesia imposes antidumping for imports Cold Rolled Coil/CRC from Japan and other countries in regulation No 65/PMK. 011/2013 of the Minister of Finance of Indonesia. In final determinations, a high margin of dumping ranging from 18,6% to 55,6% was imposed on Japanese companies.Keywords: Anti-dumping duty, Cold Rolled Coil/CRC, Dumping, Japan, Protectionism